Geospatial monitoring and structural mechanics models: a case study of sports structures - Shults, Roman; Soltabayeva, Saule; Seitkazina, Gulnur; Nukarbekova, Zhupargul; Kucherenko, Oksana (International Conference “Environmental Engineering”, 2020)
The task of geospatial monitoring is one of the most common in the practice of geodetic works. In the twentieth century, the basic principles for carrying out geospatial monitoring, accuracy calculation, observation intervals assignment, and data simulation were developed. However, since that time, both the building and geodetic technologies have been changed considerably. Among modern engineering structures, the building technology of which has undergone significant changes are sport structures. The use of the state-of-the-art sport structures is associated with the presence of specific loads, name a few: the impact of a vast number of spectators (e.g., stadiums, cycle tracks, etc.) or loads directly from the competitions equipment (e.g., bobsleigh tracks, race tracks, etc.). The primary goal of the presented paper is to develop a general approach to the preliminary accuracy calculation of the geospatial monitoring of the sports structures using the methods of structural mechanics. As an example, a football stadium was considered. Based on the simulation, the improved technology of geospatial monitoring for the sports structure was suggested. The in-depth analysis of the creation of geodetic networks for geospatial monitoring was accomplished. At the final step, the results of geospatial monitoring for the football stadium were analyzed, and hands-on recommendations were made.